Peran Fasilitator Pendamping di Remote Site (Pedesaan) Jawa dalam Mengembangkan Usaha Nasabah di BTPN Syariah Kec. Sawahan Surabaya - Mitayani, Intan; Nirawati, Lia (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Bestee Program is one of the realizations of BTPN Syariah which invites dedicated students to provide assistance which is expected to improve the entrepreneurial abilities, knowledge, soft skills and hard skills of productive underprivileged customers or mothers. Through facilitators accompanied by the Bestee Application which is used as a place to train and develop human resource capabilities to be more digitally literate in running a business so that it can survive sustainably. Introducing the precisely Daya application which can help customers in running their business. The research method used is a qualitative approach using descriptive methods. The results of this research prove that with assistance provided by facilitators, students can maintain and even increase the businesses of productive underprivileged customers of BTPN Syariah in this era of digitalization